Treatment Slow Learner Learning Repetitive Addition with Realistic Mathematics Learning Approach - Hafidah, Hafidah; Rukli, Rukli (Mimbar Sekolah Dasar, 2022)
Mathematics is the queen of science, but many children experience slow learners in these subjects. Slow learners can achieve maximum abilities if the learning approach is appropriate to the situation. This study examines slow learner children with a realistic mathematics education approach. The research method uses single subject research with multiple baseline cross conditions designs at school and home. Then data analysis uses an internal analysis approach and an analysis between curves of both conditions. The results showed that slow learners experienced a higher tendency to score higher when studying at home than at school. In addition, slow learner students have a higher score increase after treatment, but after moving to another condition, the increase in score slows or stagnates. The implication is that teachers teach slow learners with the MRE approach at school based on home situations to maximize their learning abilities.